Stability indicating Rp-UPLC method development and validation for the simultaneous estimation of fosnetupitant and palonosetron in bulk and injection dosage form - Poojari Venkatesh; Umasankar Kulandaivelu; GSN Koteswara Rao; Guntupalli Chakravarthi; Rajasekhar Reddy Alavala; Bandlamuri Rajesh (Universidade de São Paulo, 2022)
Abstract A stability indicating UPLC method has been developed and validated for the simultaneous determination of fosnetupitant and palonosetron in bulk and in injection dosage form. This combination is used for the prevention of acute and delayed nausea and vomiting associated with initial and repeated courses of highly emetogenic chemotherapy for cancer. The chromatographic analysis was performed on an HSS, RP C18 column (2.1 x 100 mm, 1.8 µm) with an isocratic mobile phase composed of 0.25 M potassium dihydrogen orthophosphate buffer (pH 6.5), pH adjusted with dilute sodium hydroxide:acetonitrile (55:45 v/v), at a flow rate of 0.5 mL/min, and the eluents were monitored at an isosbestic point of 286 nm. The developed method was validated according to the ICH guidelines pertaining to specificity, precision, accuracy, linearity and robustness, and the stability indicating nature of the method was established by forced degradation studies. The retention times of fosnetupitant and palonosetron were observed at 1.390 and 2.404 min, respectively. The developed method proved to be accurate and precise. Linearity was established between 4.70 and 14.10 µg/mL for fosnetupitant and between 0.05 and 0.15 µg/mL for palonosetron. The LOD and LOQ were 0.115 and 0.385 µg/mL, respectively, for fosnetupitant, and 0.005 and 0.016 µg/mL, respectively, for palonosetron. Therefore, the proposed UPLC method was reliable, reproducible, precise and sensitive for the quantification of fosnetupitant and palonosetron.